2018
DOI: 10.1523/jneurosci.3328-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processing of Acoustic and Electric Interaural Time Differences in Normal-Hearing Gerbils

Abstract: Bilateral cochlear implants (CIs) provide benefits for speech perception in noise and directional hearing, but users typically show poor sensitivity to interaural time differences (ITDs). Possible explanations for this deficit are deafness-induced degradations in neural ITD sensitivity, between-ear mismatches in electrode positions or activation sites, or differences in binaural brain circuits activated by electric versus acoustic stimulation. To identify potential limitations of electric ITD coding in the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 91 publications
3
5
0
Order By: Relevance
“…1b). As might be expected in light of previous studies investigating ITD sensitivity in the IC [22,24,28,29], we observed that the large majority of multi-units exhibited at least some, and at times substantial degrees of tuning to stimulus ITD.…”
Section: Ic Neurons Of Nd Rats Exhibit Varying Degrees and Types Of Isupporting
confidence: 89%
See 2 more Smart Citations
“…1b). As might be expected in light of previous studies investigating ITD sensitivity in the IC [22,24,28,29], we observed that the large majority of multi-units exhibited at least some, and at times substantial degrees of tuning to stimulus ITD.…”
Section: Ic Neurons Of Nd Rats Exhibit Varying Degrees and Types Of Isupporting
confidence: 89%
“…1b). As might be expected in light of previous studies investigating ITD sensitivity in the IC [22,24,28,29], we observed that the large majority of multi-units exhibited at least some, and at times substantial degrees of tuning to stimulus ITD.The manner in which changes in ITD changed neural discharge patterns was also highly variable from one recording site to the next. While many multi-units showed typical shortlatency onset responses to the stimulus which varied in response amplitude ( Fig.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Studies with single-neuron recordings in non-human species provide insight into the role of acoustic exposure on binaural sensitivity. In acutely deafened animals, the encoding of neurally evoked ITDs presented through electrical stimulation of a CI can provide just as accurate encoding of ITDs as those presented with acoustic stimulation [ 26 ]. This finding suggests that the length of acoustic impairment might be a key factor contributing to poor vs. good sensitivity to ITDs and not the mode of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in neural implant and electrical stimulation technologies, such as cochlear implants (CIs) and vagal nerve stimulators, increasingly rely on concurrent neural stimulation and recordings to either assess functional transformations between connected brain regions ( Lim and Anderson, 2007 ; Kral et al, 2009 ; Atencio et al, 2014 ; Hancock et al, 2017 ; Vollmer, 2018 ; Li et al, 2019 ) or to optimize electrical stimulation via closed-loop feedback control ( Wilson et al, 1991 ; Schachter and Saper, 1998 ; Dhillon and Horch, 2005 ; Lebedev and Nicolelis, 2006 ; O’Doherty et al, 2011 ; Mc Laughlin et al, 2012 ; Hartmann et al, 2014 ). In such applications, capacitive and inductive coupling between the stimulating and recording electrodes leads to stimulus-evoked artifacts in the extracellular recordings that are often several orders of magnitude larger (i.e., milli-volts) than the extracellular neural signals (typically micro-volts).…”
Section: Introductionmentioning
confidence: 99%